Covid-19 pandemic impact on the Music event industry in the Czech Republic - Dušek, Mikoláš; Escobar Rios, Andrea; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
This thesis undertakes a literature review in order to identify critical factors of customer loyalty towards music festivals as a generator of experiences in the Czech Republic during the COVID-19 pandemic. The main goal of the thesis is to understand and determine the role of digital media marketing and its importance for effective strategic communication in crisis times. It will be based on examining changes in the music festival industry during the COVID-19 pandemic and analysis of consumer behaviour of event attendees before and during the crisis.
Vedoucí práce: Andrea Escobar Rios
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses